2007
DOI: 10.1002/dvdy.21152
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus hairy2 functions in neural crest formation by maintaining cells in a mitotic and undifferentiated state

Abstract: The neural crest is a population of mitotically active, multipotent progenitor cells that arise at the neural plate border. Neural crest progenitors must be maintained in a multipotent state until after neural tube closure. However, the molecular underpinnings of this process have yet to be fully elucidated. Here we show that the basic helix-loop-helix (bHLH) transcriptional repressor gene, Xenopus hairy2 (Xhairy2), is an essential early regulator of neural crest formation in Xenopus. During gastrulation, Xhai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…135 Migration begins with the disassembly of the cell-cell adherence junction complex, and the acquisition of a mobile phenotype; cells are maintained in an undifferentiated state in part through the action of the transcription factor Hairy2. 136,137 Within the embryo, neural crest cells migrate through spaces between the basal laminae that define the basal surface of the epidermis and the developing dermomyotome. 138,139 These spaces are occupied by extracellular matrix rich in laminin and fibronectin.…”
Section: Once We Are Neural Crest We Have To Migratementioning
confidence: 99%
“…135 Migration begins with the disassembly of the cell-cell adherence junction complex, and the acquisition of a mobile phenotype; cells are maintained in an undifferentiated state in part through the action of the transcription factor Hairy2. 136,137 Within the embryo, neural crest cells migrate through spaces between the basal laminae that define the basal surface of the epidermis and the developing dermomyotome. 138,139 These spaces are occupied by extracellular matrix rich in laminin and fibronectin.…”
Section: Once We Are Neural Crest We Have To Migratementioning
confidence: 99%
“…5;Nagatomo and Hashimoto 2007). As the double inhibition of Xhairy2 and p27 xic1 rescued the phenotype of neurogenic marker up-regulation as well as the loss of LF expression of pax6 (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In other words, Xhairy2 may keep lens lineage cells competent to incoming inducing signal(s) by maintaining undifferentiated, or pluripotent, states of those cells via regulation of p27 xic1 expression. Interestingly, our previous report showed that Xhairy2 in the anterior prechordal plate mesoderm and the neural crest, which are thought to be a group of pluripotent cells, is necessary to maintain tissue identity or the undifferentiated state of such cells (Yamaguti et al, 2005;Nagatomo and Hashimoto, 2007). Maintenance of these states of cells in the presence of Xhairy2 might be in part related to the still-unknown molecular nature of lens competence, which is conceptually the basal state of ectoderm leading to lens formation (Henry and Grainger, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red arrowheads indicate repression of foxd3 expression on the injected side. The dose of morpholinos was as follows: co mo, 3.4 ng; h2A mo, 3.4 ng; h2B mo, 3.5 ng Specificity of the morpholinos was examined elsewhere with rescue experiments (Nagatomo and Hashimoto 2007).…”
Section: Resultsmentioning
confidence: 99%